2017
DOI: 10.21470/1678-9741-2016-0032
|View full text |Cite
|
Sign up to set email alerts
|

Techniques, Timing & Prognosis of Post Infarct Ventricular Septal Repair: a Re-look at Old Dogmas

Abstract: ObjectiveThe study aimed to identify the factors affecting the prognosis of post myocardial infarction (MI) ventricular septal rupture (VSR) and to develop a protocol for its management.MethodsThis was a single center, retrospective-prospective study (2009-2014), involving 55 patients with post MI VSR. The strengths of association between risk factors and prognosis were assessed using multivariate logistic regression analysis. The UNM Post MI VSR management and prognosis scoring systems (UPMS & UPPS) were deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 20 publications
(42 reference statements)
3
44
1
9
Order By: Relevance
“…A long time between MI and surgery recommends the heart is well collateralized and systems have had enough time to adjust to changed hemodynamics. They mentioned that the institution of Intra-aortic balloon pump (IABP) before surgery can stabilize the patients by reducing the afterload of the left ventricle and recovers coronary circulation [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A long time between MI and surgery recommends the heart is well collateralized and systems have had enough time to adjust to changed hemodynamics. They mentioned that the institution of Intra-aortic balloon pump (IABP) before surgery can stabilize the patients by reducing the afterload of the left ventricle and recovers coronary circulation [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies showed that earlier repair and operation in VSR patients increases the risk of mortality. It could be clarified by the fact that unstable hemodynamics and ischemia-reperfusion damage to an infarcted myocardium increases the injury of the myocardium [ 28 ]. Time is needed to restore heart muscle tissues in the necrotic part.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, an important heterogeneity concerning the timing of transcatheter closure can be observed among studies [5-10]. The current ST-elevation myocardial infarction (STEMI) guidelines of the European Society of Cardiology (ESC) and the American College of Cardiology Foundation/American Heart Association (ACCF/AHA) recommend urgent PI-VSR closure irrespective of hemodynamic status [11, 12], but the timing of PI-VSR closure and perioperative therapeutic management remain controversial [13]. In previous studies, most percutaneous device closures were performed during the subacute and chronic periods (≥2 weeks) after the initial detection of PI-VSR [4, 8, 10, 14].…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective single‐center study by Malhotra et al, reporting on 55 cases with post‐MI‐VSR aiming to identify factors affecting the prognosis of this complication, shorter intervals between VSR and surgery were found to be a strong and probably the most important predictor of mortality. It was suggested that if the surgery could be delayed for more than 3 days after the occurrence of VSR, a 50% reduction in mortality could be expected . However, it is debatable whether this conclusion could be generalized to patients with a combination of VSR and IMD.…”
Section: Discussionmentioning
confidence: 99%